Theoretical Study of Abnormal Thermal Expansion of CuSCN and Effect on Electronic Structure - Sun, Pengju; Gao, Qilong; Liu, Junzhe; Liang, Erjun; Sun, Qiang (Frontiers in Materials, 2021)
CuSCN, as a new type of inorganic hole-transporting semiconductor with a wide bandgap (>3.4 eV), is attracting much attention in the fabrication of perovskite solar cells. In this article, by using first-principles density functional theory (DFT) and the quasi-harmonic approximation (QHA) approach, we have studied lattice dynamics and abnormal thermal expansion of the system, including α- and β-CuSCN phases. The influence of the abnormal thermal expansion of the lattice on the electronic structure, especially on the bandgap of the system, was explored and discussed. We found that due to the shearing modes and the three acoustic modes along the direction of the c-axis, the α- and β-CuSCN show a negative thermal expansion (NTE) in the direction of the c-axis. The torsion modes of the Cu–N–C–S atomic chains in the α-CuSCN may lead to an NTE in the directions of the a, b-axes of the α-phase. As a result, our theoretical results demonstrated that the α-CuSCN exhibits an anisotropic bulk NTE. While the β-CuSCN displays a strong uniaxial negative thermal expansion in the direction of the c-axis, in the directions of the a, b-axes, it exhibits positive thermal expansion. Our DFT calculations also predicted that the α-CuSCN has a direct bandgap, which increases slightly with increasing temperature. However, the β-CuSCN has an indirect bandgap at low temperature, which converts to a direct bandgap near the temperature of 375 K due to the strong positive expansion in the ab plane of the phase. Our work revealed the mechanisms of the abnormal thermal expansion of the two phases and a strong coupling between the anisotropic thermal expansion and the electronic structures of the system.